Processos de aprendizagem no contexto da economia solidária: um estudo baseado no interacionismo interpretativo - Garcia, Edilene de Oliveira Pereira (2015)
This study aims to understand the processes of learning in the context of the solidarity economy. The participants are entrepreneurs belonging to the Association of Craftsman and Artists of Diadema (Sao Paulo - Brazil). The research question is "how the learning processes of cooperation, self-management, solidarity and economic action are developed by entrepreneurs of solidarity economy belonging to an association of craftsmen in order to act in this type of economy? ". The overall objective is to identify, describe and analyze how they develop the learning processes of cooperation, self-management, solidarity and economic action. Specific aims are to identify who are the subjects of learning (how they are defined and where they are located), why they learn (the reasons that lead to learning), what they learn (what are the contents and what are the outcomes of learning) and how they learn (what are the key actions of the learning processes). This is a critical qualitative and interpretative study which theoretical framework is composed of two approaches: interpretive interactionism (Denzin, 2001) and social learning theory (Elkjaer, 2003). These approaches converge and put the experiences undergone by people in their everyday life as starting points for understanding social phenomena. The field research is contextualized from the concepts and landmarks presented by Singer (2002), França-Filho (2007), Lechat (2002), Gaiger (2003) and Silva (2011) and the Ministry of Labor and Employment of Brazil (BRAZIL, 2012). Interpretive interactionism is also used to guide the methodological procedures. The organization chosen to carry out the research was the Association of Craftsman and Artists of Diadema (São Paulo Brazil). It represents an opportunity to enter a field that today is little explored in studies of organizational learning. To capture the phenomenon eight interviews were conducted with seven craftswoman and with the president of the Association. The recorded material and transcripts originated life histories of thick description. The analysis of recurring features of life histories led to the recognition of five instances where there are the learning experiences of interaction - and the epiphanies which directly or indirectly lead to the learning of cooperation, self-management, solidarity and economic action. These instances are: the family, the individual, the other , the entity of social economy and local government . Learning processes as identified and analyzed in this study considers the influence of power operating in the context. In this sense, it was found that, under the AAAPD, the learning processes of the basic elements of solidarity economy remains tied to local government initiatives and strategies. The entity maintains strong dependency relationship with local government what constitutes the main difficulty in conducting its activities and disseminating, experiencing and manifesting collectively the principles of solidarity economy. This study helps to increase knowledge about learning in different organizational contexts from those of traditional private economy and the impact of social environments in these processes. It also serves as a reference for the use of interpretive interactionism as a theoretical-methodological approach in studies in the field of organizational learning.